Rancang Bangun Sistem Operasional Budidaya Tambak Ikan Kerapu Berbasis Android (Studi Kasus: Kelompok Tani Bhakti Usaha 2) - Ahmad Shofiudin firdani Wafa; Nurudin Santoso; Lutfi Fanani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Aquaculture is the maintenance and preservation of fish or other aquatic organisms, one of them namely riparian fish grouper. Production of grouper in Indonesia itself is quite high and also continue to experience increased almost every year. But there are problems that writers get from farmers Group of Bhakti Usaha 2, that farmers often occurrence of error permberian feed meratanya not cause growth of grouper, as well as errors in the calculation of the period of harvest so that farmers are insufficient in terms of the results obtained, this is because all the process of cultivation is still done by manual so that the fault of the humans (human error) is still often the case. The solution given by the author is making the system operational riparian android-based grouper with features to provide scheduling at each activity will be carried out by the pond grouper farmers, from the time of preparation budidadaya to the process of harvesting, logging detail and also the recording of financial results. On the development of this system using the method of iterative model. Results from testing the system unit was found to be 100% valid values as well as been testing which also get value 100% valid. The resulting values of usability testing for a very satisfying on the three aspects of the test and an aspect worth satisfying.